2017
DOI: 10.1007/s00586-017-5205-5
|View full text |Cite
|
Sign up to set email alerts
|

New method for correction of lumbo-sacral kyphosis deformity in patient with high pelvic incidence

Abstract: Bilateral longitudinal sacral osteotomy appears to be a safe and efficient way of correcting the sagittal imbalance caused by an extremely high PI. Although technically demanding, it achieves good radiological and functional outcomes and avoids entering the spinal canal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The technique involved longitudinal osteotomies through the sacral ala and derotation of the sacrum to achieve the desired pelvic incidence. At one year after surgery, the patient reportedly maintained a balanced sagittal alignment [14].…”
Section: Discussionmentioning
confidence: 99%
“…The technique involved longitudinal osteotomies through the sacral ala and derotation of the sacrum to achieve the desired pelvic incidence. At one year after surgery, the patient reportedly maintained a balanced sagittal alignment [14].…”
Section: Discussionmentioning
confidence: 99%
“…An additional 7 studies were identified involving sacral dome osteotomies or osteotomies with transitional lumbar anatomy. 4,[18][19][20][21][22][23] When including these data, the rate of L5-related neurological deficit was 23% (12 of 52 patients), with most resolving over time. The results are summarized in Table.…”
Section: Literature Reviewmentioning
confidence: 99%